2019
DOI: 10.1111/his.13806
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage repair alterations are frequent in prostatic adenocarcinomas with focal pleomorphic giant‐cell features

Abstract: Aims: Prostatic adenocarcinomas with focal pleomorphic giant-cell features constitute a rare tumour subtype with abysmal clinical outcomes. More than one-third of patients with this histology die within a year of the initial diagnosis of prostate cancer. We aimed to perform molecular profiling of these tumors to identify potential therapeutic targets. Methods and results: Here, we performed next-generation sequencing with a highly validated targeted panel (UW-OncoPlex) on somatic tumour DNA extracted from eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
(53 reference statements)
0
17
0
1
Order By: Relevance
“…Prostate adenocarcinomas with focal pleomorphic giant cell features are rare prostate cancer subtype with dismal clinical prognosis. A recent study reported the genetic analysis of 8 cases of prostatic adenocarcinomas with focal pleomorphic giant cell features, showing that DNA damage repair mutations are common, with two out of eight having biallelic pathogenic mutations in homologous DNA repair genes and two out of eight having biallelic pathogenic mutations in mismatch repair genes ( MSH2 and MLH1 ) [156].…”
Section: Most Recurrent Genetic Abnormalities Observed In Prostatementioning
confidence: 99%
“…Prostate adenocarcinomas with focal pleomorphic giant cell features are rare prostate cancer subtype with dismal clinical prognosis. A recent study reported the genetic analysis of 8 cases of prostatic adenocarcinomas with focal pleomorphic giant cell features, showing that DNA damage repair mutations are common, with two out of eight having biallelic pathogenic mutations in homologous DNA repair genes and two out of eight having biallelic pathogenic mutations in mismatch repair genes ( MSH2 and MLH1 ) [156].…”
Section: Most Recurrent Genetic Abnormalities Observed In Prostatementioning
confidence: 99%
“…5 Recently, Lotan et al studied eight prostatic adenocarcinomas with pleomorphic giant-cell features, and found DNA damage repair mutations but not ERG fusions. 7 ADT, androgen deprivation therapy; IHC, immunohistochemistry. *A low-grade prostatic adenocarcinoma had a positive ERG fluorescence in-situ hybridisation result, but the sarcomatoid component was negative; this was interpreted as two unrelated tumour clones.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few studies assessing a handful of cases have examined the molecular characteristics of these rare variants. [4][5][6][7] A better understanding of the molecular features of these tumour variants could shed light on the clinical and biological diversity of prostate cancer, and potentially have therapeutic significance. We studied a cohort of rare prostatic carcinoma variants, including adenosquamous carcinoma, sarcomatoid carcinoma, and pleomorphic giant-cell carcinoma, for their molecular profiles, using fluorescence in-situ hybridisation (FISH) and next-generation sequencing (NGS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Presence of HRD is associated with aggressive histological features including Gleason pattern 5 and intraductal/ductal prostate carcinoma. [58][59][60][61][62] In one of the first trials, olaparib demonstrated greatest efficacy in mCRPC patients harbouring genetic alterations in genes directly or indirectly involved in HRD. 63 Recently published data from the phase 3 PROfound trial provide further evidence for olaparib activity in mCRPC with HRD, especially in patients with BRCA1, BRCA2, or ATM alterations.…”
Section: Homologous Recombination Dna Repair Deficiencymentioning
confidence: 99%